The Renaissance of the Vocal Art : A Practical Study of Vitality, Vitalized Energy, of the Physical, Mental and Emotional Powers of the Singer, through Flexible, Elastic Bodily Movements - Myer, Edmund J. (Edmund John), 1846-1934 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Renaissance of the Vocal Art" by Edmund J. Myer is a practical study on vocal training written in the early 20th century. The book explores the principles of voice production, emphasizing the importance of natural bodily movements and emotional energy in achieving artistic singing. Myer critiques previous singing methods, advocating for a holistic approach that aligns with nature's laws and enhances the singer's physical, mental, and emotional faculties. The opening of the book introduces readers to Myer's motivation and perspective on vocal art, outlining the evolution of singing techniques from the Old Italian School through the Dark Ages to the modern pursuit of a natural approach. He asserts that previous methods have often relied on artificial practices, hindering vocal freedom and expression. Myer stresses the significance of flexible movements, self-expression, and the development of emotional energy$1 (Ba concept he describes as the "singer's sensation." This foundation sets the stage for his systematic approach to vocal training, which the following chapters will delve into further. (This is an automatically generated summary.)s
Release date is 2004-07-08
Produced by David Newman and PG Distributed Proofreaders
Keywords: Singing -- Instruction and study